Comprehensive Assessment of Economic Losses from Premature Mortality of the Population in Regions - Kozlova, Olga A.; Zubarev, Nikolay Yu. (Economy of Regions, 2020)
Since the demographic situation in the Russian Federation is characterised by high mortality of the economically active population, it is necessary to assess significant economic and social losses for the country and its regions. In this regard, the importance of the research lies in developing a methodology to assess economic losses from premature mortality of the population. We hypothesise that both the loss of production of goods and services and the volume of their consumption determine the value of economic losses from premature mortality, which can be differentiated by gender, age and causes of death of the population, depending on regional characteristics. As the main research methods, we applied statistical data analysis using the methodology of the System of National Accounts (SNA). Then, we proposed a methodological approach to a comprehensive assessment of economic losses from premature mortality of the population based on three differentiating features such as gender, age, and cause of death. Moreover, we structure economic losses, depending on the components of the gross regional product in the present and in the future. We have substantiated the feasibility of considering the consumption of goods and services by the unemployed population aged from 0 to 72 years in the structure of economic losses from premature mortality. We tested the methodology on the statistical database of Federal State Statistic Service (Rosstat) for the Perm region in the period 2009 — 2017. The methodological approach allowed us to comprehensively analyse the economic losses from premature mortality of the population in the region. In contrast to those strategies described in the academic literature, our methodology provides a more complete assessment of the magnitude of economic losses, allowing the selection of effective tools for regional health policy.